Techniques to enhance english listening comprehension skills in senior students of unidad educativa UPSE, La Libertad, Santa Elena province, school year 2021-2022 - Picazo Suarez, Adriana Milena (2021)
Listening comprehension is a critical language skill to master when learning a second language. However, language learners consider listening comprehension to be the most complex communicative skill to learn. Although the role of listening comprehension in language teaching has been repeatedly emphasized, many Ecuadorian teachers do not give adequate recognition to this skill in the classroom. In this paper, some issues related to listening comprehension skills have been reviewed to provide selected techniques to improve listening comprehension abilities in UPSE senior students. It begins by describing listening comprehension problems in Ecuadorian schools, a brief theoretical foundation of this skill, and a few methods to develop it, followed by the methodology used for data collection and, finally, the proposal of a specific technique to enhance listening comprehension skills in senior students.